The importance of negotiation and conflict management - Tabassum, Iubna (Journal of Management and Science, 2020)
In this paper, we will discuss in detail about negotiation and conflict management and its approaches which is necessary everywhere. We will also discuss the steps and stages of negotiation and conflict management. Highlight the important features between the two relationships in almost every field and four - dimensional approach of negotiation and conflict management. We suggest adopting all stages and steps everywhere to sort out issues and problems related to negotiation and conflict management. There are various research and topics which talked about it and suggested many things to handle it, same in this paper present all important aspects of the topic and discuss it in detail and its importance in the emerging technological world. Also, areas that generally adopt negotiation and conflict management for a smooth run of business, organization,personal relationship, and bonding between people for the long term.